Management of Post-Traumatic Composite Bone and Soft Tissue Defect of Leg - Ravi K. Mahajan; Krishnan Srinivasan; Mahipal Singh; Adish Jain; Taha Kapadia; Ankush Tambotra (Indian Journal of Plastic Surgery)
Management of composite defects of leg following trauma requires a planned ortho-plastic approach right from the outset. Timely, planned intervention results in reduced amputation rates and improved limb salvage and function. Right from the time of presentation of the patient to the emergency with such injury, the process of decision making in terms of salvage or amputation, local flap cover/free flap cover, bone reconstruction first or soft tissue or both combined, come into play. Guidelines on management are unclear for such defects, a literature search yielding various methods being used by different authors. This article is a review of current literature on management of composite leg defects. A summary of the literature search in terms of various management options given by various authors including the rationale, advantages and disadvantages of each strategy has been provided in this article. The management protocol and method followed by the author in his institute for management of such composite defects have been described in detail. The article seeks to provide readers with an understanding of the management strategies so that appropriate method could be chosen to provide best result.